Screening Lansia Sehat Dengan Kontrol Gula Darah Di Panti Werdha Sumarah Sukomoro - Novita Anggrain; Margareta Haiti; Mustika Sari Hutabarat; Lidwina Septie Ch; Aprida Manurung (IAI Darussalam, 2021)
Old age is a natural process experienced by both men and women who have reached the age of 60 years and over. Aging means that you have experienced a process of decline both physically and mentally. The elderly can still be productive when they have a healthy and fit body. Health can be maintained through a balanced nutritional intake and through regular health checks. Efforts to prevent disease in the elderly can be carried out through health checks and providing counseling so that the elderly understand so that further complications do not occur. Through this activity, the elderly are expected to be able to live healthy lives in their daily lives. Counseling activities were carried out to 31 elderly people at the Sumarah Sukomoro Nursing Home in Palembang City by checking their blood pressure and blood sugar. As a result, there were 4 people with sugar levels > 200 mg/dl, 8 people with sugar levels 140-199 mg/dl, 18 people with sugar levels < 140 mg/dl, and only 1 person who was not willing to be tested. So from these results it can be seen that most of the elderly have a risk of developing diabetes. Therefore, it is hoped that the elderly can change their lifestyle, which begins with improving their diet and regulating regular physical activity, such as starting to walk and other physical activities to prevent generative complications.